A case of formic acid poisoning: prompting for a different line of management - Nayanatara, Vasireddy Nayanatara; Ravitheja, Jampani (International Journal of Research in Medical Sciences, 2019)
Formic acid is an easily available substance and can thus be consumed voluntarily or accidentally. Here is a case who presented to our center 5 days post accidental ingestion of formic acid. He had developed acute renal failure requiring hemodialysis. Post admission he had altered sensorium probably alcohol withdrawal and later aspiration pneumonia and ARDS. He developed a late onset GI bleed on day 8 of ingestion with significant hemoglobin drop. An emergency endoscopy was done which showed a normal esophagus but extensive corrosive damage and active bleeding from gastric area. He continued to have drop in hemoglobin in-spite of aggressive volume and blood product transfusions. He was taken up for an emergency subtotal gastrectomy and viable tissue was demarcated with intraoperative endoscopy and a subtotal gastrectomy was performed. He stabilized initially but worsened again 2 days later with worsening lactic acidosis and succumbed to his illness. The fact that esophagus was completely spared with extensive involvement of stomach could possibly indicate a need for review of initial management of corrosive/organic acid poisoning.